Penyelesaian Sengketa Dalam Perspektif Antropologi Hukum - Muhammad Ilham; M Taufiq (P3M dan Jurusan Syariah dan Ekonomi Bisnis Islam STAIN Sultan Abdurrahman Kepulauan Riau, 2021)
The purpose of this paper is to find a meeting point for the study of legal anthropology in national law that has been in effect in Indonesia. Indonesia's plural society makes it richer in terms of prevailing customs. Of course, each custom has its own ways and criteria for establishing and compiling norms that apply in society. This, as the National law, as the unifier of the prevailing laws in society, certainly seeks to make absolute provisions and implement justice. This study seeks to find common ground for these matters, so that the study used is a qualitative approach by suggesting the normative side of legal settlement that applies in society. The results of this study found that there is a meeting point in the study of legal anthropology if it is related to the concept of national law. This effort, of course, must be understood by law enforcers so that every dispute can be preceded by an anthropological aspect of law. This action is expected to have a side of justice that will emerge so that every problem will be able to be resolved.